`The Influence of Situational Leadership, Organizational Culture, Work Motivation, Work Environment, and Job Satisfaction on the Employee Performance - Liawren Anzelina; Hananiel M. Gunawan (Feedforward: Journal of Human Resource, 2026)
This research aims to examine the influence of situational leadership, organizational culture, work motivation, and work environment on the performance of Gen Z employees at PT Agung Sedayu Group, with job satisfaction as a moderating variable. This study employs an associative quantitative method using a purposive sampling technique on 115 Gen Z employees at PT Agung Sedayu Group. Primary data were collected through questionnaires and analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The results of data analysis show that situational leadership, organizational culture, work motivation, work environment, and job satisfaction each have a direct, positive, and significant influence on the performance of Gen Z employees. Job satisfaction was found to be the predictor with the strongest influence. Furthermore, this research found that job satisfaction significantly strengthens the positive influence of situational leadership, organizational culture, work motivation, and work environment on employee performance. These findings provide theoretical implications by enriching human resource management literature and practical insights for PT Agung Sedayu Group to optimize the performance of Gen Z employees.